1990
DOI: 10.1111/j.1432-1033.1990.tb19320.x
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of binding of the benzamidine‐ and arginine‐based inhibitors Nα‐(2‐naphthyl‐sulphonyl‐glycyl)‐dlp‐amidinophenylalanyl‐piperidine (NAPAP) and (2R,4R)‐4‐methyl‐1‐[Nα‐(3‐methyl‐1,2,3,4‐tetrahydro‐8‐quinolinesulphonyl)‐l‐arginyl]‐2‐piperidine carboxylic acid (MQPA) to human α‐thrombin

Abstract: The X-ray crystal structure of the trypsin complex formed with N"-(2-naphthyl-sulphonyl-glycyl)-~~-pamidinophenylalanyl-piperidine (NAPAP) was determined with X-ray data to 0.18-nm resolution and crystallographically refined. NAPAP binds into the active site of trypsin in a quite compact form: the pamidinophenylalanine moiety of the D-stereoisomer binds into the specificity pocket; the glycyl group is hydrogen bonded with Gly216; the naphthyl group stands perpendicular to the indole moiety of Trp215; the piper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(52 citation statements)
references
References 34 publications
(22 reference statements)
4
48
0
Order By: Relevance
“…Both recombinant native and mutant thrombins retained the ability to bind benzamidine (Fig. 2), a reversible inhibitor of serine proteases which specifically occupies the small substrate binding pocket/S 1 subsite (25). The recombinant mutant thrombins were also able to bind and sequester the fluorogenic thrombin substrate D-Phe-Pro-Arg-AFC, thereby blocking its hydrolysis by native thrombin (data not shown).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Both recombinant native and mutant thrombins retained the ability to bind benzamidine (Fig. 2), a reversible inhibitor of serine proteases which specifically occupies the small substrate binding pocket/S 1 subsite (25). The recombinant mutant thrombins were also able to bind and sequester the fluorogenic thrombin substrate D-Phe-Pro-Arg-AFC, thereby blocking its hydrolysis by native thrombin (data not shown).…”
Section: Resultsmentioning
confidence: 91%
“…Recombinant prothrombin production was determined by enzyme-linked immunosorbent assay (ELISA) and Western blots and the highest yielding clones were grown to confluence in a 24,000-cm2 surface cell "factory" (Nunc, Inter Med, Naperville, IL) in minimum essential medium (MEM) a-nucleoside-deficient medium with 80 nM methotrexate, 100 U/ml penicillin, 100 .g/ml streptomycin, 25 mM Hepes buffer, 5 $ig/ml vitamin K, 0.2 mg/ml proline, and 10% dialyzed bovine calf serum. When the cultures reached full confluence, all medium was removed, all growing surfaces were washed six times with phosphate-buffered saline to remove contaminating bovine prothrombin and thrombin, and cells were grown in MEM a-nucleoside-defi-cient medium containing 100 units/ml penicillin, 100 gg/ml streptomycin, 25 mM Hepes buffer, 5 jg/ml vitamin K, 0.2 mg/ml proline, 1 gg/ml insulin and 5 ytg/ml transferrin for 36-48 h. Recombinant S205A prothrombin was purified from conditioned media by anion exchange chromatography (12), diluted to -100 Ig/ml in 150 mM NaCl, 10mM Tris-HCl, pH 7.4, 0.5% polyethylene glycol (PEG) 6000, and treated for 1 h with prothrombinase complex as previously described (I13). pH was then changed to 7.0 with 1 M HCl and the S205A mutant thrombin-containing solution treated with an -1,000-fold molar excess of (p-amidinophenyl)methanesulfonyl fluoride (APMSF)' to inhibit factor Xa and any bovine thrombin that might contaminate the preparation.…”
Section: Methodsmentioning
confidence: 99%
“…Another important observation of the structural studies is that the major distinction between the substrate binding cleft of t-PA and u-PA occurs in the region corresponding to the aryl binding site of thrombin (2,3,36). In u-PA this pocket is partially filled by an insertion of two amino acids (threonine 97A, leucine 97B; chymotrypsin numbering) that is absent in t-PA. Consequently, the aryl biding site is significantly larger in t-PA than in u-PA.…”
Section: Contribution Of Structural Studies To Understanding Restrictmentioning
confidence: 99%
“…Various X-ray diffraction studies [24][25][26][27][28][29][30] of thrombin-inhibitor clarified that the thrombin active site is mainly defined by the specificity S1 pocket, the hydrophobic Ppocket, and the hydrophobic D-pocket, as is shown in Figs. 1 and 2.…”
Section: )mentioning
confidence: 99%
“…Complexes of human or bovine a-thrombin with synthetic arginyl peptides have been analyzed by X-ray diffraction studies. [24][25][26][27][28][29][30] The X-ray data suggested that the thrombin active site consists of the specificity (S1) pocket, the hydrophobic proximal pocket (P-pocket), and the hydrophobic distal pocket (D-pocket). The guanidino nitrogen atoms of inhibitors form a salt bridge with Asp189 (numbering of the thrombin amino acid residues is based on the chymotrypsinogen nomenclature introduced by Bode et al) 24,28) in S1 pocket, and additional favorable interactions between the inhibitor and D-pocket or P-pocket enhance the inhibitory potency.…”
mentioning
confidence: 99%